Refleksi Etika Politik Islam dalam Pembentukan Lembaga Yudikatif - Nurul Rezkyani S; Nur Syamsi; Kurniati Kurniati (Mandub : Jurnal Politik, Sosial, Hukum dan Humaniora, 2024)
The application of Islamic political ethics has unique characteristics in every country, including Indonesia. Even though Indonesia does not officially claim to apply Islamic concepts, if one examines the 1945 Constitution, there are indications that Indonesia refers to Islamic principles. This research aims to evaluate the concept of Islamic political ethics in the formation of judicial institutions in Indonesia. The approach used is qualitative with a literature review method, namely by looking for various references from books and journals regarding the reflection of Islamic political ethics in the formation of judicial institutions. This research began by looking for several references regarding Islamic Political Ethics to take points from each concept that was discussed. Stated.